2017
DOI: 10.14393/bj-v33n2-32739
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis identified rainfall homogeneous regions in Tocantins state, Brazil

Abstract: ABSTRACT:Identifying homogeneous regions regarding the monthly rainfall is relevant in agricultural planning, especially in relation to the installation of crops. Thus, the aim of this study was to apply the cluster analysis using Ward's algorithm to identify homogeneous regions in Tocantins State. Rainfall database of 34 stations (sites) of Tocantins, from 1976 to 2012, it were obtained of the Database of the Agência Nacional de Águas, Instituto Nacional de Meteorologia and Serviço Meteorológico do Brasil. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…However, the station (649000) did not present any occurrence of the reduction of the mixed exponential (Figure 5), and this one is also inserted in the Amazon–Cerrado ecotone biome, however, the station is further north of HR II. According to Oliveira Junior et al (2017), this region is more influenced by the rainfall regimes of the Amazon region. Thus, the ecotone regions should be analyzed more carefully.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the station (649000) did not present any occurrence of the reduction of the mixed exponential (Figure 5), and this one is also inserted in the Amazon–Cerrado ecotone biome, however, the station is further north of HR II. According to Oliveira Junior et al (2017), this region is more influenced by the rainfall regimes of the Amazon region. Thus, the ecotone regions should be analyzed more carefully.…”
Section: Resultsmentioning
confidence: 99%
“…What motivates this study is the importance of the TAHR in the Brazilian context because, among its resources, the hydroelectric and mineral production and its vocation for agribusiness are outstanding; thus, knowledge of the temporal and spatial variability of the precipitation is indispensable (Oliveira Junior, Xavier, Teodoro, Gois, & Delgado, 2017; Silva Junior et al, 2019). Thus, this study aims to evaluate the applicability of four CDFs (exponential, two‐parameter exponential, mixed exponential, and gamma) to estimate the probability of occurrence of daily rainfall in the TAHR.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have opted for cluster analysis in identifying homogeneous rainfall regions, e.g., Terassi et al [23], Lyra et al [24], Goyal et al [25] and Oliveira-Junior et al [26]. However, the approaches and the algorithms used to perform the cluster analysis are inherently different.…”
Section: Cluster Analysismentioning
confidence: 99%
“…2019 series (Dourado et al, 2013). Oliveira-Júnior et al (2017) reported that the identification of homogeneous zones was fundamental for agricultural planning. Marzban and Sandgathe (2006) showed that clustering is an effective algorithm when using observed meteorological data.…”
Section: Introductionmentioning
confidence: 99%